Pengaruh Aplikasi Trichokompos terhadap N-Tersedia dan Pertumbuhan Vegetatif Rosella Merah (Hibiscus sabdariffa) - Muhammad Miftah Farid; Rabiatul Wahdah (Universitas Lambung Mangkurat, 2026)
Red rosella (Hibiscus sabdariffa) is a horticultural plant with high economic value because its flower petals are rich in anthocyanins, which are beneficial as antioxidants. However, rosella productivity in Indonesia is still low due to limited nutrient availability, especially nitrogen (N) in the soil. One improvement effort is carried out through the application of trichocompost, an organic fertilizer resulting from the decomposition of organic matter with the help of Trichoderma sp. which functions to increase nutrient availability and improve soil properties. This study aims to determine the effect of trichocompost application on nitrogen availability (available N) and to determine the best dosage for rosella vegetative growth. The study was conducted from June–September 2024 using a one-factor randomized block design (RBD) with four trichocompost dosage levels: 20, 25, 30, and 35 tons ha⁻¹. The parameters observed included plant height, number of leaves, number of branches, and available N (N-NO₃⁻) and (N-NH4+) content of the soil 14 days after planting. The results showed that trichocompost application was able to increase the vegetative growth of roselle, indicated by a significant increase in plant height, leaf number, and branch number. A dose of 30 t/ha produced the highest number of leaves, while a dose of 35 t/ha played a greater role in increasing plant height and branch number. However, trichocompost application did not significantly increase available N in the soil at 14 days after planting, which is thought to be due to the longer nitrogen mineralization process. Thus, trichocompost is effective in improving the vegetative growth of roselle, but is not optimal in increasing soil nitrogen availability in the early incubation phase..